Viennese late enlightenment and the early socialist calculation debates: Rationalities and their limits - Alexander Linsbichler (Duke University, Center for the History of Political Economy (CHOPE), 2021)
Austrian economist Ludwig Mises's central role in the socialist calculation debates has been consensually acknowledged since the early 1920s. Yet, only recently, Nemeth, O'Neill, Uebel, and others have drawn particular attention to Mises's pertinent encounter with one of the most colorful characters of 'Red Vienna': logical empiricist and 'skeptic utopist' Otto Neurath. Despite several surprising agreements, Neurath and Mises certainly provide different answers to the questions 'what is meant by rational economic theory' (Neurath) and whether 'socialism is the abolition of rational economy' (Mises). However, previous accounts and evaluations of the exchange between Neurath and Mises suffer from attaching little regard to highlighting their idiosyncratic uses of the term 'rational'. The paper at hand reconstructs and critically compares the different conceptions of rationality defended by Neurath and Mises and suggests some consequent insights with respect to Viennese Late Enlightenment, contemporary rationality wars, the socialist calculation debates, and the foundations of welfare economics.
Keywords: B13; B14; B24; B25; B41; B51; B53; P16; P21; P51; 330; rationality; enlightenment; socialist calculation debates; Otto Neurath; Ludwig Mises; Vienna Circle; Austrian School of Economics; knowledge; welfare economics